Bird species define the relationship between West Nile viremia and infectiousness to Culex pipiens mosquitoes. - Jefferson A Vaughan; Robert A Newman; Michael J Turell (Public Library of Science (PLoS), 2022)
The transmission cycle of West Nile virus (WNV) involves multiple species of birds. The relative importance of various bird species to the overall transmission is often inferred from the level and duration of viremia that they experience upon infection. Reports utilizing in vitro feeding techniques suggest that the source and condition of blood in which arboviruses are fed to mosquitoes can significantly alter the infectiousness of arbovirus to mosquitoes. We confirmed this using live hosts. A series of mosquito feedings with Culex pipiens was conducted on WNV-infected American robins and common grackles over a range of viremias. Mosquitoes were assayed individually by plaque assay for WNV at 3 to 7 days after feeding. At equivalent viremia, robins always infected more mosquitoes than did grackles. We conclude that the infectiousness of viremic birds cannot always be deduced from viremia alone. If information concerning the infectiousness of a particular bird species is important, such information is best acquired by feeding mosquitoes directly on experimentally infected individuals of that species.